Tools Supporting the Measurement of Fair Play in Sport - Hideg, Gabriella (Central European Journal of Educational Research, 2022)
In the course of our work so far, we have repeatedly emphasized the loss of morality and value in societies, which has an impact on all areas of life (including sport). Today, we are far from the original values of sport and the ideals of Baron Coubertin; fair play as pure play. Among the ethical issues of sport, special attention should be given to two extremes: fair play and doping. In our study, we aimed to review the available literature related to the topic of fair play in both the domestic and international setting. In selecting the processed research, our main goal was to present results that are useful for Hungarian educational science, including specific, internationally validated fair play attitude surveys and educational programs. Our current study is the first theoretical partial result of a larger-scale research, which includes the Hungarian adaptation of the presented tests.